Occupational Therapy in Fatigue Management in Multiple Sclerosis: An Umbrella Review. (21st March 2019) - Angela, Salomè; Tullia, Sasso D'Elia; Giorgia, Franchini; Valter, Santilli; Teresa, Paolucci
Abstract : Background. Fatigue is one of the most invalidant symptoms of Multiple Sclerosis (MS) that negatively affects occupational and work performance and social participation. Occupational therapy (OT) assessment and treatment of impairments related to fatigue can have a significant and positive impact on the quality of life. Methods. An umbrella review has been carried out to provide rehabilitative decision makers in healthcare with insight into the role of OT in fatigue management in Multiple Sclerosis. The question is, what type of treatment provided by occupational therapist is more effective in reducing fatigue in Multiple Sclerosis? A search of literature published until June 2018 was undertaken by three independent reviewers using PubMed, PEDro, and Cochrane Library database including systematic reviews and meta-analyses of the last 10 years. Results . 10 studies were selected (5 systematic reviews, 1 meta-analysis, 3 reviews, and 1 guideline). Conclusions. Fatigue management programs have moderate evidence; other strategies such as OT strategies and telerehabilitation show low evidence.